Metode EMPUK (Ember Tumpuk) Untuk Mengolah Sampah Dapur Menjadi POC (Pupuk Organik Cair) - Yora, Muharama; Renfiyeni, Renfiyeni; Chrisnawati, Chrisnawati; Meyuliana, Aulia; Ilham, Dewi Jayagma; Mahmud, Mahmud; Nelvi, Yusmi; Afrini, Delsi; Harissatria, Harissatria; Afrahamiryano, Afrahamiryano (Jurnal Pengabdian Kepada Masyarakat Mahaputra Muhammad Yamin, 2024)
The increase in population is proportional to the increase in the amount of waste generated. Solid waste that is not treated properly can become a nesting place for various germs that are detrimental to human health and damage the aesthetics of the environment. Piles of untreated waste can pollute water, soil and air. As a result, it is necessary to differentiate waste into organic and inorganic categories. This waste can be used to make organic fertiliser. This programme aims to teach the women of PKK RT 001/RW 004 in Simpang Rumbio Village, Lubuk Sikarah Sub-district, Solok City how to make liquid organic fertiliser using household waste. This activity involves teaching, socialisation of activities, counselling, and discussion about making liquid organic fertiliser. The result of this activity is that PKK women have the potential to be able to make organic fertiliser starting at the household scale which can be used for plant care and the fertiliser can be harvested after 2 to 3 weeks of fermentation.